The United Kingdom and the negotiation of the 1969 New York Convention on Special Missions - Young, John W. (Taylor & Francis (Routledge), 2014)
During 1968-69, members of the United Nations, meeting in the Legal Committee of the General Assembly, negotiated a Convention on Special Missions, sometimes known as the New York Convention, setting out the privileges and immunities of ad hoc embassies between states. The negotiation was part of a process through which the UN sought to clarify the status and rights of official representatives, so that diplomacy could function with security and certainty. This article looks at the role of one leading power, the United Kingdom, in the talks. It explores how British interests were defined, the tactics used to secure them and how London came to terms with pressure from other states to redefine its approach. The focus is on the overall political thrust of the British negotiating position, as formulated mainly by the Foreign Office, rather than the detailed talks on such thorny issues as tax avoidance and diplomatic property. The articles shows that, while London was keen to see a codification of diplomatic law, Cold War considerations made it less than enthusiastic about an upsurge in the number of special missions that the New York Convention might encourage.